2009
DOI: 10.1074/jbc.m808705200
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis Protein Kinase K Modulates Activation of Transcription from the Promoter of Mycobacterial Monooxygenase Operon through Phosphorylation of the Transcriptional Regulator VirS

Abstract: Mycobacterium tuberculosis encodes for 11 eukaryotic-like serine/threonine protein kinases. Genetic and biochemical studies show that these kinases regulate various cellular processes including cell shape and morphology, glucose and glutamine transport, phagosome-lysosome fusion and the expression, and/or activity of transcription factors. PknK is the largest predicted serine/threonine protein kinase in M. tuberculosis. Here, we have cloned, overexpressed, and purified protein kinase K (PknK) to near homogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 56 publications
(79 reference statements)
1
56
0
Order By: Relevance
“…The PknK C terminus is a multidomain regulatory region that contains an AAA motif encompassing an ATP/GTP binding site (P loop), a PDZ domain (a common structural domain of 80 to 90 amino acids found in the signaling proteins of bacteria, yeast, plants, and animals [27]), and a region consisting of superhelical (SUPR)-or tetratricopeptide (TPR)-like repeats (1,28) (Fig. 7A); however, their roles in PknK function have not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PknK C terminus is a multidomain regulatory region that contains an AAA motif encompassing an ATP/GTP binding site (P loop), a PDZ domain (a common structural domain of 80 to 90 amino acids found in the signaling proteins of bacteria, yeast, plants, and animals [27]), and a region consisting of superhelical (SUPR)-or tetratricopeptide (TPR)-like repeats (1,28) (Fig. 7A); however, their roles in PknK function have not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Kumar et al have shown that replacement of lysine at position 55 in PknK Mtb by methionine (K55M) abolishes PknK kinase activity (27); thus, an M. smegmatis strain overproducing PknK Mtb K55M mutant protein was constructed (LIX80 [Table 1]). We confirmed the overexpression of the pknK K55M gene in induced LIX80 cell lysates by immunoblotting (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations